2012
DOI: 10.1080/17461391.2011.641032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and types of sports training on QT variables in young elite athletes

Abstract: Maximum and minimum QTc were significantly longer in female athletes than in male athletes (max: 414.2 vs. 404.5 ms, min: 375.1 vs. 359.2 ms, p<0.0001 respectively), whereas QTc dispersion (QTcD) was shorter in female athletes than in male athletes (39.2 vs. 45.3 ms, p<0.0001). QTcD was significantly shorter in female athletes than in the female control group (39.2 vs. 45.2 ms, p<0.05). However, no statistically significant difference was observed between male athletes and the male control group. Male gymnasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
3
19
2
1
Order By: Relevance
“…This can be explained on the basis of physiological changes induced by exercise on autonomic nervous system. On grouping our subjects on the basis of gender, irrespective of parental history of diabetes, we observed that females exhibited a slightly longer QTc as is already reported in the literature [13,28]. The females showed a post exercise lengthening of QTc whereas the male subjects exhibited an exercise induced shortening of QTc.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This can be explained on the basis of physiological changes induced by exercise on autonomic nervous system. On grouping our subjects on the basis of gender, irrespective of parental history of diabetes, we observed that females exhibited a slightly longer QTc as is already reported in the literature [13,28]. The females showed a post exercise lengthening of QTc whereas the male subjects exhibited an exercise induced shortening of QTc.…”
Section: Discussionsupporting
confidence: 59%
“…The corrected QT interval is referred to as the QTc. Gender also affects QTc interval with females observed to be having a longer QTc interval [13]. The autonomic nervous system affects QTc interval, independent of heart rate, as revealed by pacing studies [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…The same results were received in other works. For example Kazuto Omiya et al [28] studied dynamic and dispersion of QT intervals in athletes of different kinds of sports and in peoplenot sportsmen. No statistically significant differences were found between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…El área de la investigación en artes marciales aún en la actualidad es un campo fértil que ofrece innumerables posibilidades, debido a que la mayoría de estudios se enfocan al deporte de alto rendimiento, dejando de la lado la práctica deportiva de forma lúdica; ejemplo de ello son los estudios realizados en España sobre el judo, por Reche, Tutte y Ortín (2014) o los de Ściślak, Rokita, y Błach (2015) Aunque los trabajos realizados desde principios de siglo en diversos contextos mundiales han sido abundantes, casi nunca han abordado el clima motivacional en el judo centrándose en los niveles no profesionales; los estudios de Vertonghen et al (2014), definen las características psicosociales de los deportistas de artes marciales; el estudio de Omiya et al (2014) o el de Pocecco y Burtscher (2013), establecen diferencias por género en multitud de especialidades deportivas entre ellas el judo, pero en ningún caso analizan la motivación en niveles competitivos no profesionales.…”
unclassified